The Centenary of Immune Thrombocytopenia—Part 2: Revising Diagnostic and Therapeutic Approach - Consolini, Rita; Costagliola, Giorgio; Spatafora, Davide (Frontiers in Pediatrics, 2017)
Primary immune thrombocytopenia (ITP) is the most common cause of thrombocytopenia in children and adolescents and can be considered as a paradigmatic model of autoimmune disease. This second part of our review describes the clinical presentation of ITP, the diagnostic approach and overviews the current therapeutic strategies. Interestingly, it suggests an algorithm useful for differential diagnosis, a crucial process to exclude secondary forms of immune thrombocytopenia (IT) and non-immune thrombocytopenia (non-IT), which require a different therapeutic management. Advances in understanding the pathogenesis led to new therapeutic targets, as thrombopoietin receptor agonists, whose role in treatment of ITP will be discussed in this work.